Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1098/rsif.2019.0199
|View full text |Cite
|
Sign up to set email alerts
|

Spider silk colour covaries with thermal properties but not protein structure

Abstract: Understanding how and why animal secretions vary in property has important biomimetic implications as desirable properties might covary. Spider major ampullate (MA) silk, for instance, is a secretion earmarked for biomimetic applications, but many of its properties vary among and between species across environments. Here, we tested the hypothesis that MA silk colour, protein structure and thermal properties covary when protein uptake is manipulated in the spider Trichonephila plumipes .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, it is well known that pigment plays an important role in ultraviolet (UV) survival [ 35 ], and UV reflection is an important aspect of prey attraction by spider webs [ 36 ]. In terms of the ecological implication of the spider silk pigment, this prey attraction and web camouflage has been studied in detail [ 26 ], and the color has been reported to affect only the thermal properties of the silk [ 37 ]. However, prolonged exposure to UV radiation damages silk, and silkworm silk naturally use sericin coating to provide protection to UV damage by downregulating oxidative stress [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well known that pigment plays an important role in ultraviolet (UV) survival [ 35 ], and UV reflection is an important aspect of prey attraction by spider webs [ 36 ]. In terms of the ecological implication of the spider silk pigment, this prey attraction and web camouflage has been studied in detail [ 26 ], and the color has been reported to affect only the thermal properties of the silk [ 37 ]. However, prolonged exposure to UV radiation damages silk, and silkworm silk naturally use sericin coating to provide protection to UV damage by downregulating oxidative stress [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the core structure seems no influence on variations within species regarding the color of the silk 9 . This can be supported by the fact that different spiders, for instance, some Argiope species have yellow silk fibers while producing silks of much different protein expressions 9 . In addition, silks other than major ampullate silk, for instance, viscous capture silks of Trichonephila spiders can be yellow in color 10 …”
Section: Introductionmentioning
confidence: 98%
“…The golden pigment is believed to be used for condition‐dependent courtship signaling 8 . The pigmentation of silk fibers might be associated with thermal properties 9 . Osaki et al 18,19 investigated the difference in the ultraviolet (UV) tolerance between the silk fibers produced by diurnal and nocturnal spiders and found that the dragline silk fibers of diurnal spiders maintained and even improved the mechanical strength under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Example 2: Our work on the optical properties of spider dragline silk has shown that the silk's textured surface and crystalline structures primarily influences its colouration (Blamires et al, 2019). Examining the surface features of the silk more closely might thus enable us to copy the fibers' surface textures to create chromogenic fabrics incorporating micro-scale weave structures and knots to create unique colourations without using dyes or pigments.…”
mentioning
confidence: 99%